Evaluating the Risk-Benefit Profile of Corticosteroid Therapy for COVID-19 Patients: A Scoping Review - Daniel Hsiang-Te Tsai; Emma Harmon; Jan Goelen; Heather E. Barry; Li-Yang Chen; Yingfen Hsia (MDPI AG, 2024)
Background: The 2019 coronavirus (COVID-19) outbreak was declared a global pandemic in March 2020. It quickly spread across all continents, causing significant social, environmental, health, and economic impacts. During the pandemic, there has been consideration of repurposing and repositioning of medications, such as corticosteroids, for the treatment of hospitalised COVID-19 patients. Objective: To assess and summarise corticosteroid regimens used for hospitalised COVID-19 patients, focusing on dosage, route of administration, and clinical outcome from clinical trials. Methods: PubMed and Embase databases and the grey literature were searched to identify randomised controlled trials (RCTs) that evaluated the efficacy of corticosteroids in hospitalised patients with COVID-19 between January 2020 and January 2023. This scoping review was conducted in line with the PRISMA extension for scoping reviews (PRISMA-ScR) checklist. Key findings: A total of 24 RCTs were eligible for inclusion. There was variation in the steroid regimens used for treatment across COVID-19 trials. Despite the heterogeneity of included RCTs, the overall results have shown the benefits of improving lung function and a lower all-cause mortality rate in hospitalised COVID-19 patients treated with systematic corticosteroids. Conclusions: Corticosteroids have proven to be an effective treatment for COVID-19 patients in critical condition. However, comparative effectiveness studies should be conducted to assess the efficacy and safety of optimal corticosteroid treatment at the population level. Moreover, the global burden of long COVID is significant, affecting millions with persistent symptoms and long-term health complications. Thus, it is also necessary to evaluate the optimal steroid regimen for long COVID treatment.